Influence of virus citrus tristeza (CTV) of Tahití lime (Citrus latifolia Tanaka), grafted on rootstocks of cleopatra mandarin (Citrus reshni Horth. Ex Tan) (Revista Sistemas de Producción Agroecológicos, 2014)
The Tahiti lime (Citrus latifolia T) cultivation, is one of the economic lines contributing to exports in Colombia, however, production is affected by various factors that cause losses, among which the most limiting is the "virus citrus sadness" (CTV), affecting their productivity. This research was directed to conduct an analysis of the disease in ecological conditions of the Eastern Plains of Colombia, where the virus has reduced production n 90%, after the ninth year after being established as a crop and sixth year after having entered the production phase. Data were obtained CORPOICA Research Center, La Libertad, a cash crop of Tahiti lime, planted in the year 1997 and Cleopatra pattern. Information collected in 2003 by researchers at the center and compared with the information obtained to the date of this work was analyzed, data as incidence and severity of CTV on the crop, and the influence of these factors on production were evaluated through time, moreover, the symptoms present in different parts of the plant. The results of the observations and assessments culture Tahiti lime established CORPOICA La Libertad in the year 1997 was affected for eleven years by the CTV, presenting an incidence gradually increased up to 100%, 490 trees/ha established, all are with CTV. Importantly, since the ninth year the crop has a notable reduction in fruit size and quality and therefore their productivity because of this disease.
Keywords: citrus; fruit; production